Capcanele unei întâlniri cu tâlc. Relaţia dintre text şi imagine în cultura română premodernă şi receptarea ei în contemporaneitate - Cristina Bogdan (Revista de Istorie și Teorie Literară)
The present paper aims at passing over several of the issues of old Romanian culture, starting from the crucial relationship between the literary and the iconographic discourses. The major directions of our approach concern three aspects: the identification of research sites that might bring into play the intersection between texts, folklore creations and iconographic representations; analysing the relation between the image and the look it is reflected in, according to the socio-cultural context we take into consideration (that of the emergence of the image and today’s one respectively), with a special focus on the faces of Death that are inserted, over the 18th–19th centuries, in the iconography of the worship monuments in Muntenia; sketching a possible research site in danger because of the absence of an exhaustive corpus of images: the relation between the iconographic sequence and the caption that goes with it.